2011
DOI: 10.4067/s0718-40262011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevida global y por estadios de 137 pacientes con cáncer intraoral: Experiencia del Instituto Nacional del Cáncer

Abstract: Analysis of survival of 137 patients with oral cancerBackground: Oral cancer accounts for 1% of cancer mortality. It is more common in men but its frequency is increasing in women due to their growing smoking habits. Aim: To report the experience in the management of a cohort of patients with oral cancer. Material and Methods: Review of medical records of patients with oral cancer treated between 1989 and 2004. Demographic and clinical data were recorded and survival was determined examining death certifi cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
5
2
1
9
Order By: Relevance
“…In the present study, the percentage of patients diagnosed with oral SCC who survived 5 years (27.8%) was similar to Santos et al [26] (28.4%) and De Oliveira et al [27] (24%); however, it was lower than other studies, such as Bórquez et al [23] (57%), Arriagada et al [25] (58.4%), Honorato et al [28] (43.1%), Montoro et al [29] (39%), and De Araújo Daher et al [30] (38.71%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the percentage of patients diagnosed with oral SCC who survived 5 years (27.8%) was similar to Santos et al [26] (28.4%) and De Oliveira et al [27] (24%); however, it was lower than other studies, such as Bórquez et al [23] (57%), Arriagada et al [25] (58.4%), Honorato et al [28] (43.1%), Montoro et al [29] (39%), and De Araújo Daher et al [30] (38.71%).…”
Section: Discussionsupporting
confidence: 89%
“…Santos et al [32] reported mean survival higher in patients with stage II (10 years), while in stage IV it was 3.7 years. In the study by Bórquez et al [23], the survival for stages I, II, II, and IV was 86%, 67%, 52%, and 51%, respectively. These findings confirm the early diagnosis of oral cancer as an important step in increasing survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…La supervivencia se ve altamente afectada por el estadio; a medida que este aumenta, aumenta la probabilidad de muerte, lo que sugiere la coherencia de los estudios sobre la plausibilidad biológica del estadio como factor pronóstico. 3,17,[27][28][29][30][31] Como limitaciones del estudio, fue imposible cotejar los certificados de defunción que poseen las instituciones gubernamentales con la información de las historias clí-nicas, lo cual disminuyó el número de pacientes incluidos en el análisis. Además, el rastreo de los pacientes por medio de llamadas telefónicas no permitió conocer el fenómeno de forma real, por lo que se requirió la colaboración de entes gubernamentales como el DANE para el acceso a la información de la causa básica de muerte y la fecha de defunción de los pacientes.…”
Section: Discussionunclassified
“…Survival is highly affected by tumor stage; the higher the stage the higher the likelihood of death, which is consistent with studies on the tumor stage as a biological possibility of prognostic factor. 3,17,[27][28][29][30][31] Limitations of the present study include the impossibility to check death certificates in government institutions against information from medical records, which reduced the number of patients included in the analysis. In addition, tracking patients through phone calls makes it difficult to analyze the actual phenomenon, requiring the cooperation of government bodies such as the Departamento Administrativo Nacional de Estadística (DANE) to access information of underlying causes and date of death.…”
Section: Discussionmentioning
confidence: 99%
“…Otro estudio 22 , lo encontró asociado sólo en un 29,8%. Un alto porcentaje de pacientes evaluados (96,5%) recibieron tratamiento, siendo el más frecuente la cirugía asociada a radioterapia (57,2%), similar a otro estudio 32 en Chile, donde 62,04% recibieron la misma terapia combinada. A diferencia de esto, Peña y cols 31 , reveló que sólo 15,2% recibió cirugía y radioterapia.…”
Section: Discussionunclassified